2022
DOI: 10.1186/s12885-022-10425-6
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancers in men under the age of 50: about a series in Togo, Sub-Saharan Africa

Abstract: Background Prostate cancer is a public health problem and increasingly diagnosed in men under 50 years of age. This cancer occurs much more in subjects of advanced age, generally over sixty. The aim of the study was to describe the epidemiological, clinical and histopathological aspects of prostate cancer in men under the age of 50 in Togo. Methods It was a retrospective descriptive, cross-sectional study of histologically confirmed cases of prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…These results are similar to those of Tengue et al who described symptoms of the lower urinary tract in 89.2% [9]. Darré et al had also found functional urinary signs in 37.93% [12]. This high frequency of functional urinary disorders could be explained by the fact that they constitute a nuisance in daily life forcing the patient to consult.…”
Section: Data Related To Late Diagnosis Of Prostate Cancersupporting
confidence: 90%
See 2 more Smart Citations
“…These results are similar to those of Tengue et al who described symptoms of the lower urinary tract in 89.2% [9]. Darré et al had also found functional urinary signs in 37.93% [12]. This high frequency of functional urinary disorders could be explained by the fact that they constitute a nuisance in daily life forcing the patient to consult.…”
Section: Data Related To Late Diagnosis Of Prostate Cancersupporting
confidence: 90%
“…Histologically, these were adenocarcinomas in 99% and squamous cell carcinoma in 1%. These were only adenocarcinomas in the series by Darré et al [12]. A predominance of prostate adenocarcinomas was also reported by Ndoye et al in 97.7% of cases [16].…”
Section: Data Related To Late Diagnosis Of Prostate Cancersupporting
confidence: 63%
See 1 more Smart Citation